Principles of macroeconomics - Ruffin, Roy.; Gregory, Paul R. (Glenview, Ill. : Scott, Foresman, 1983)
The book provides the most modern treatment of macroeconomics that is currently available at the time the book was published.
Also issued in a combined volume with Principles of microeconomics, under title: Principles of economics.
Includes bibliography and index.
uaj 15/04/2015
Loan
Keywords: Macroeconomics